1990
DOI: 10.1063/1.345191
|View full text |Cite
|
Sign up to set email alerts
|

The role of hydrogen in diamond synthesis using a microwave plasma in a CO/H2 system

Abstract: In order to clarify the role of hydrogen in diamond synthesis using a microwave plasma in a CO/H2 system, carbon films were grown by varying hydrogen mole fractions in a CO/H2/He microwave plasma. The correlation between film properties and plasma species was investigated through film characterization and plasma emission spectroscopy. C and C2 were formed in the gas phase of the CO/He system and only sootlike carbon was deposited. Hydrogen additions to the CO/He system were found to enhance diamond growth by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…Muranaka et al have proposed that CO on the diamond surface can react with excited molecular hydrogen from the plasma, leading to C incorporation in the diamond phase and H adsorbed on the diamond surface. 5,6 The general features of this simple model are consistent with the results of Fig. 6.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Muranaka et al have proposed that CO on the diamond surface can react with excited molecular hydrogen from the plasma, leading to C incorporation in the diamond phase and H adsorbed on the diamond surface. 5,6 The general features of this simple model are consistent with the results of Fig. 6.…”
Section: Discussionsupporting
confidence: 88%
“…1-6 Furthermore, additions of O-containing atoms to the gas source can improve the diamond film quality, resulting in a lower nondiamond ͑or sp 2 -bonded͒ carbon content, and allowing diamond growth to be extended to lower substrate temperatures while retaining high quality. [7][8][9][10][11][12][13][14][15][16][17] It has been first suggested 3,5,18 and later demonstrated 19 that most of the diamond phase generated by a plasma of CO and H 2 with CO/H 2 ϳ0.05 results from the conversion of CO to hydrocarbon species with the initial step being CO excitation by energetic plasma electrons. In contrast to CH 4 /H 2 mixtures, from which high quality diamond films can be obtained only if CH 4 /H 2 Ͻ0.02, 20 CO/H 2 mixtures yield high quality films over a very wide range 2 -at least two orders of magnitude in the CO/H 2 dilution ratio, from 0.04 to ϳ5, as shown below.…”
Section: Introductionmentioning
confidence: 99%
“…Density functional theory ͑DFT͒ calculations, 34 motivated by the experimental observation of deposition of diamond films by C 2 produced from C 60 fragmentation in hydrogen poor plasmas, 47,48 showed that growth by C 2 at a bare ͑i.e., not H terminated͒, clean diamond ͑110͒ surface is also energetically favored, and presents only very low energy barriers to the formation of C 2n chains and, ultimately, new layers. Although there have been reports of increasing C 2 concentrations in low power microwave plasmas that are correlated with degraded diamond film quality, 49,50 Gruen et al observed a positive correlation between C 2 emission and the film growth rate, and OES studies by our group 6 and by others 8 demonstrated that growth of high quality diamond films can proceed hand in hand with strong C 2 dϪa emission in more highly activated gas plasma environments.…”
Section: Discussionmentioning
confidence: 90%
“…20 can degrade the diamond quality because it makes the etching process of non-sp 3 bonding by the hydrogen atoms insufficient. The C 2 radical illustrated in Ref.…”
Section: Resultsmentioning
confidence: 99%